Factors associated with postnatal care seeking behavior among mothers of infants - Sarkar, Juthi; Yasmin, Farida; Biswas, Debashis; Uddin, M. Imtiaz; Nowshin, Sharmina; Ferdous, Fahmida; Rahman, M. Moklesur; Shafiuzzaman, M. (International Journal of Research in Medical Sciences, 2024)
Background: Postnatal period is a critical phase in the lives of mothers and newborn babies. Lack of appropriate care during this period could result in significant ill health and even death. Hence the study was carried out to identify the factors associated with postnatal care seeking behavior among mothers of infants. Methods: This descriptive type of cross-sectional study was conducted at EPI centers of Sadar upazilla of Magura district from January to December 2023 among purposively selected 384 rural women of reproductive age who had at least one living child aged between 6 weeks to 10 months after obtaining ethical clearance from ethical review committee (ERC) of Dhaka Medical College. Results: The average age of respondents was 24.28±3.52 years, with 84.1% aged 18-27 years. Among mothers, 59.6% completed primary education, while 10.2% reached secondary or higher education levels. Most (91.1%) were housewives, with 57% residing in joint families. While most of participants received ANC, only 35.5% sought PNC. The primary reasons for avoiding PNC included lack of awareness (28.9%) and financial constraints (23.7%). Significant associations were found between PNC utilization and mothers’ education, delivery complications, and decision-making authority within the family (p<0.05). Conclusions: To improve utilization of postnatal care, national and local level action plan should be introduced to promote postnatal care delivery. PNC awareness campaign, motivation and economic empowerment programs for targeting mothers from the impoverished area need to be implemented.